Traditional Security Risk Assessment Methods In Cloud Computing Environment: Usability Analysis - Sameer Hasan Albakri; Bharanidharan Shanmugam; Ganthan Narayana Samy; Norbik Bashah Idris; Azuan Ahmed (Penerbit UTM Press, 2024)
Volume: 73 No: 2 Special Issue on International Conference of Recent Trends in Information and Communication Technology (IRICT 2014)